IMPLEMENTASI STRATEGI PEMBELAJARAN AKTIF DALAM MENINGKATKAN PRESTASI BELAJAR AKIDAH AKHLAK PESERTA DIDIK MA NURUL IMAN KAB. TASIKMALAYA JAWA BARAT - Abdul Aziz Hilmy Haidar (UNISAN JURNAL, 2024)
This research examines the implementation of active learning strategies in improving students' Akidah Akhlak learning achievement at MA Nurul Iman, Tasikmalaya Regency, West Java. Active learning strategies are important to deepen the understanding and application of religious values in everyday life. The focus of the research is to understand how the strategy is implemented, its impact on students' understanding and learning achievement, as well as stakeholder perceptions of its effectiveness. This research method uses a qualitative approach with data collection techniques through classroom observations, interviews and document analysis. The research results show that active learning strategies have been implemented routinely at MA Nurul Iman, by actively involving students in the learning process. The impact includes increasing students' understanding, motivation and learning achievement in the Aqidah Akhlak subject. However, there are several challenges in implementing this strategy, including limited time, resources and technological skills. This research provides valuable insights for the development of more effective and efficient learning practices at MA Nurul Iman. It is hoped that the results can become a reference for developing better religious education policies in the region. Keywords: Active Learning, Learning Achievement